Strategi Komunikasi Pt Pln Nusantara Power Services Dalam Membentuk Persepsi Profesionalisme Melalui Instagram @Pln_Npservices - Adhelia Intan Putri Derawan; Tira Fitriawardhani; Julyanto Ekantoro (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study raises the issue of PT PLN Nusantara Power Services' communication strategy in shaping perceptions of professionalism through Instagram @pln_npservices. In the context of the important role of social media as a means of representing a company's image, especially in the electricity industry, which requires public trust. The research focuses on understanding the digital communication strategies implemented and the factors that influence the formation of professionalism perceptions among audiences. The research method used is qualitative with a descriptive approach, through in-depth interviews with relevant parties, observation, and documentation to collect relevant data on the planning and implementation of the strategies. The results of the study show that the communication strategy used by PT PLN Nusantara Power Services includes five stages according to Hafied Cangara, namely research, planning, implementation, evaluation, and reporting. Content that highlights the company's achievements, awards, technical education on electricity, and operational activities reflects professionalism. This study confirms that a structured digital communication strategy can contribute to the formation of perceptions of professionalism, but its effectiveness will increase if the company adds audience needs research and strengthens visual creativity and two-way interaction in content management.